Mutant Prevention Concentrations of Four Carbapenems against Gram-Negative Rods - Credito, Kim (American Society for Microbiology (ASM), 2010)
We tested the propensities of four carbapenems to select for resistant Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, and Acinetobacter baumannii mutants by determining the mutant prevention concentrations (MPCs) for 100 clinical strains with various ß-lactam phenotypes. Among the members of the Enterobacteriaceae family and A. baumannii strains, the MPC/MIC ratios were mostly 2 to 4. In contrast, for P. aeruginosa the MPC/MIC ratios were 4 to ≥16. The MPC/MIC ratios for β-lactamase-positive K. pneumoniae and E. coli isolates were much higher (range, 4 to >16 μg/ml) than those for ß-lactamase-negative strains.